PIDA‐Promoted Selective C5 C−H Selenylations of Indolines via Weak Interactions. Issue 21 (12th September 2019) - Gu, Linghui; Fang, Xinyue; Weng, Zhengyun; Lin, Jiafu; He, Meicui; Ma, Wenbo
Abstract: An efficient PIDA (phenyliodine(III) diacetate)‐promoted positional selective C−H selenylations of indolines with diaryl diselenides has been developed. This transformation conducted under mild reaction conditions with a broad functional group tolerance, thus providing an efficient protocol to selenylated indolines. Preliminary mechanistic studies indicated a SET pathway was likely involved in this selenylation reaction. Abstract :